Innovations in Intelligent Machines-4 Recent Advances in Knowledge Engineering - Faucher, Colette.; Faucher, Colette.; Jain, Lakhmi C.; Jain, Lakhmi C. (Studies in Computational Intelligence,, 2014)
This research volume is a continuation of our previous volumes on intelligent machine. It is divided into three parts. Part I deals with big data and ontologies. It includes examples related to the text mining, rule mining and ontology. Part II is on knowledge-based systems. It includes context-centered systems, knowledge discovery, interoperability, consistency and systems of systems. The final part is on applications. The applications involve prediction, decision optimization and assessment. This book is directed to the researchers who wish to explore the field of knowledge engineering further.